2021
DOI: 10.1093/geroni/igab046.2952
|View full text |Cite
|
Sign up to set email alerts
|

Development and Initial Evaluation of the Caring Through COVID-19 Psychotherapy Group for Family Care Partners

Abstract: Dissemination of geriatrics research usually occurs through conference presentations or publications viewed by colleagues in the same field. Older adults and their family caregivers have limited direct access to research findings. We sought to pilot a direct-to-caregiver workshop with the intent to disseminate geriatrics research directly to family caregivers of older adults. As part of an academic national conference, an ‘Updates in Geriatrics Research’ workshop is presented as a compilation of innovative res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…To provide quality care to their loved ones, caregivers need to receive support. Studies have shown that caregivers who have access to better social support are healthier and can better care for their loved ones [ 29 , 30 ]. However, less is known about the potential of self-help groups for family caregivers of nursing home residents.…”
Section: Introductionmentioning
confidence: 99%
“…To provide quality care to their loved ones, caregivers need to receive support. Studies have shown that caregivers who have access to better social support are healthier and can better care for their loved ones [ 29 , 30 ]. However, less is known about the potential of self-help groups for family caregivers of nursing home residents.…”
Section: Introductionmentioning
confidence: 99%